Functionalized cellulose nanocrystals as a novel adsorption material for removal of boron from water. (December 2021) - Wahib, Sara A.; Da'na, Dana A.; Ashfaq, Mohammad Y.; Al-Ghouti, Mohammad A.
Abstract: This study aims to prepare a novel adsorbent containing cellulose nanocrystals (CNC) isolated from date pits (DP) and ionic liquid (IL). The prepared composite of CNC and IL was then loaded onto the DP to prepare IL-CNC@DP adsorbent. The boron remediation capability was then investigated using the prepared adsorbent and compared to that of DP. The results showed the superior performance of IL-CNC@DP as compared to DP. The maximum adsorption capacity of 97 mg/g and 69 mg/g was obtained with IL-CNC@DP and DP, respectively. This can be attributed to the high surface area of 4.254 m 2 /g for IL-CNC@DP as compared to 2.126 m 2 /g for DP. The effect of pH, temperature, and initial boron concentration on adsorption was also studied. It was noticed that the % removal of boron from water increased with pH and reached its maximum of around 97% at pH 6. On the other hand, there was no effect of temperature (25 °C, 35 °C, and 45 °C) on adsorption capacity noted for both adsorbents. The results also indicated that the adsorption of boron from water by the prepared adsorbent favors the Dubinin-Radushkevich isotherm model. Graphical abstract: Image 1 Highlights: The groundwater of Qatar is contaminated with a high concentration of boron. This case study was conducted for the adsorptive removal of boron from water. The biomass-derived adsorbent was prepared for this purpose. The adsorption capacity of 97 mg/g for boron was noted for the prepared adsorbent. Thermodynamic studies showed that the prepared adsorbent favors the Dubinin-Radushkevich isotherm model.